BIÓPSIA NA ODONTOLOGIA - Sobolevsk, Cleiton; Simon, Giulia; Casaril, Ana Carolina; Stofell, Jaine; Takemoto, Marcos Massaro; Tomazelli, Karin Berria (Anais de Odontologia / ISSN 2526-9437; v. 3 n. 1 (2018): 2018/1, 2018)
.